Atayal部落國小低年級文化回應課程知識傳遞探究 An Investigation Into Culturally Responsive Curriculum Knowledge Transfer in the Lower Grades of the Atayal Tribal Elementary School - 簡良平 Liang-Ping Jian (臺灣教育社會學研究, 2022)
研究者繼Atayal部落國小低年級文化回應課程（ culturally responsive curriculum, CRC）知識選擇探究之後，本研究延續教育現場資料聚焦討論CRC知識傳輸方式及其教學特徵。本研究依據臺灣北部宜蘭地區Atayal部落國小B低年級實施CRC之質性資料，分析與詮釋個案教師如何提升學童語文及認識文化能力的歷程。歸納個案教師傳遞課程知識之策略與特徵有五點： 一、本案「Atayal男狩獵、女織布」主題課程能統整適合二年級學童學習的文化內容；二、以敘事之認識論規劃敘事文本閱讀、聆聽敘事與敘說經驗及模擬傳統技能等活動是恰當的文化傳輸策略；三、應用現代科技及學科概念教學，學童能獲得文化相關之學科知識；四、多樣的閱讀活動設計，能提升學童參與程度及國字正確率；五、個案教師課室師、生話語權分配比例趨向均等。本研究討論與建議︰一、文化認同度高的教師能積極轉化文化知識及均等分配學童學習機會；二、傳輸CRC知識之教師應具備閱讀教學、跨文化理解、學科教學等能力，較易達成CRC的多重目標。 This study is based on the author’s previous exploration of knowledge selection in a culturally responsive curriculum (CRC) for students in lower grades of the Atayal tribal elementary schools. The present manuscript provides a focused discussion of knowledge transfer methods and teaching features based on on-site CRC educational materials. A qualitative research approach explored the implementation of CRC for lower-grade students at the Atayal tribal elementary school in northern Taiwan in order to analyze and interpret the processes by which the teachers successfully improved students’ language outcomes and cultural understanding. Five key findings can be summarized in terms of the strategies and teaching features used by teachers for CRC knowledge transfer: (1) the curriculum topic of “Atayal boys to become hunters and girls to become weavers” suitably integrated cultural content for the second grade students’ learning; (2) cultural transmission strategies involved the design of learning activities based on the epistemology of narrative, including reading ethnic texts, listening to elders’ narratives, and simulating traditional skills; (3) modern technology and subject-based concept instruction were used to help students successfully acquire culturally relevant subject knowledge; (4) the design of diverse literacy activities encouraged students to actively participate in ethnicnarrative discussions, enhancing Chinese literacy strategies, and improving their accuracy in writing Chinese characters; and (5) the distribution of discourse power between teachers and students in the classroom tended to be equal. This paper discusses and proposes two recommendations: (1) teachers with high levels of cultural identity are best able to actively transform CRC knowledge and ensure equality of learning opportunities for students; and (2) teachers responsible for CRC knowledge transmission should possess skills related to literacy instruction, ethnic cultural identity, cross-cultural understanding, and subject teaching in order to easily achieve the multiple goals of the CRC.